Identification of an effective nondestructive technique for bond defect determination in laminate composites—A technical review. (November 2018) - Asif, Muhammad; Khan, Muhammad A; Khan, Sohaib Z; Choudhry, Rizwan S; Khan, Kamran A
Laminate composites are commonly used for the production of critical mechanical structures and components such as wind turbine blades, helicopter rotors, unmanned aerial vehicle wings and honeycomb structures for aircraft wings. During the manufacturing process of these composite structures, zones or areas with weak bond strength are always issues, which may affect the strength and performance of components. The identification and quantification of these zones are always challenging and necessary for the mass production. Non-destructive testing methods available, including ultrasonic A, B, and C-Scan, laser shearography, X-ray tomography, and thermography can be useful for the mentioned purposes. A comparison of these techniques concerning their capacity of identification and quantification of bond defects; however, still needs a comprehensive review. In this paper, a detailed comparison of several non-destructive testing techniques is provided. Emphasis is placed to institute a guideline to select the most suitable technique for the identification of zones with bond defects in laminated composites. Experimental tests on different composite based machined components are also discussed in detail. The discussion provides practical evidence about the effectiveness of different non-destructive testing techniques.